Membuka Peluang Berwirausaha Untuk Pemberdayaan Anak Berkebutuhan Khusus - Ibnu Syamsi (Jurnal Pendidikan dan Kebudayaan, 2010)
The purpose of study is to make a device of the development of entrepreneurship training, the develop a model of the entrepreneurship training, and to creat the material of entrepreneurship training for the special need child in community. The study employs research and development as the method and uses qualitative and quantitative as the approaches. After a series of trial is conducted, the real field operational test is performed by using pre-test and post-test design. The data is collected through interviews, participative observations, intensive discussion, documentation study, and questioners. Further, it is analyzed using descriptive analysis and inferential statistics using mark-test. The result of this study embrace the development of proper design of entrepreneurship training device for the children with special need, the development of the model of entrepreneurship training for the special need child, and the development of effective entrepreneurship training material for the applicant of the fresh entrepreneur in the special need child, that can increase one’s skill in running a business. ABSTRAKPenelitian ini bertujuan unutuk mengembangkan pelatihan kewirausahaan dan materi kewirausahaan dalam rangka pemberdayaan anak berkebutuhan khusus di masyarakat. Metode yang digunakan research and development atau penelitian dan pengembangan, dengan cara pendekatan kualitatif dan kuantitatif. Setelah melakukan serangkain uji coba, kemudian dilakukan uji operasional lapangan yang sebenarnya dengan model pretest and post design. Pengumpulan data menggunaka cara wawancara, observasi partisipatif, diskusi intensif, studi dokumentasi dan angket. Analisis data yang digunakan dengan deskriptif dan uji statistik inferensial dalam hal ini menggunakan uji–tanda. Hasil penelitian yang diperoleh rancangbangun peluang berwirausaha dan bentuk pelatihan yang tepat diterapkan untuk pemberdayaan anak berkebutuhan khusus, materi kerwirausahaan yang cocok diterapkan untuk anak berkebutuhan khusus, efektivitas bentuk pelatihan dan materi kerwirausahaan untuk anak berkebutuhan khusus untuk meningkatkan kemampuannya dalam berwirausaha.